2003
DOI: 10.1161/01.atv.0000065196.61663.8d
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Atherosclerosis Is Associated With Variation in the α 1 -Antitrypsin Gene

Abstract: Disease progression is associated with variation in AAT, and low AAT levels promote atherogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 27 publications
2
51
0
Order By: Relevance
“…This observation suggests that endogenous levels of AAT prevent infection of HIV-1. In fact, adding exogenous human AAT to latently-infected cell lines reduced production of HIV-1 in vitro (49). Thus, steady-state levels of AAT appear to provide a certain degree of HIV-1 infection inhibition.…”
Section: Binding Targets That Are Unrelated To Protease Inhibitionmentioning
confidence: 97%
See 1 more Smart Citation
“…This observation suggests that endogenous levels of AAT prevent infection of HIV-1. In fact, adding exogenous human AAT to latently-infected cell lines reduced production of HIV-1 in vitro (49). Thus, steady-state levels of AAT appear to provide a certain degree of HIV-1 infection inhibition.…”
Section: Binding Targets That Are Unrelated To Protease Inhibitionmentioning
confidence: 97%
“…In addition, studies point at a direct relationship between AAT and apolipoprotein B on LDL particles (47,48), and AAT-LDL complexes have been detected in human atherosclerotic lesions (48). In support of a therapeutic implication for such an association, a protective role for AAT in atherosclerosis was demonstrated in the Lipid Coronary Angiography Trial that evaluated male participants after coronary bypass surgery (49); the authors of the trial concluded that low AAT levels are associated with increased occurrence of atherogenesis.…”
Section: Binding Targets That Are Unrelated To Protease Inhibitionmentioning
confidence: 99%
“…To date, variations in the peroxisome proliferator-activated receptor ␣ gene, PPARA L162V and intron 7G Ͼ C (14), the stromelysin gene, MMP3 5A/6A (15), the platelet endothelial cell adhesion molecule-1 gene, PECAM1 53G Ͼ A (16), and the ␣ -1-antitrypsin gene, AAT V213A and 11478G Ͼ A (17), have all shown significant associations with the progression of atherosclerosis in LOCAT, with AAT V213A showing a pharmacogenetic interaction with the response to gemfibrozil treatment. In contrast, variation in the hepatic lipase (HL) gene LIPC Ϫ 514C Ͼ T, although showing strong association with HL activity and lipid parameters, showed no association with atherosclerosis progression (18).…”
mentioning
confidence: 99%
“…Inhibition of A1AT uptake by cigarette smoke may further weaken the A1AT protective role in the lung. In the last decade other physiological roles of A1AT have been discovered, such as roles in atherogenesis (Talmud et al, 2003), angiogenesis (Huang et al, 2004), fibroblast proliferation, and procollagen synthesis (Dabbagh et al, 2001). …”
Section: Physiological Roles Of Alpha-1-antitrypsinmentioning
confidence: 99%